Development of an Inquiry Based and Deep Learning Animate Physics Module with 4D Models to the Develop Stage - Maisaroh, Mukholiffatul; Toifur, Moh.; Okimustava (Kasuari: Physics Education Journal (KPEJ), 2025)
This research aims to develop an animate physics module based on an inquiry approach and deep learning. The method used is Research and Development (R&D) with a 4D model consisting of the Define, Design, Develop, and Disseminate stages. The research was carried out up to the Develop stage which includes analysis of the curriculum, materials, and student needs (Define).module structure design (Design); and expert validation and limited trials (Develop).The research instruments consisted of an expert validation questionnaire, a student response questionnaire, and learning outcome tests (pretest and posttest). The validation results showed that the module obtained a score of 87% (very suitable) from material experts, 85% (very suitable) from media expert, and 83% (suitable) from language experts. Limited trials on 25 grade XI students showed a practicality score of 86% (very practical). Furthermore, student learning outcomes improved, with an average pretest score of 58.4, a posttest score of 80.6, and an N-Gain of 0.062 (medium-high category). These findings demonstrate that the inquiry based and immersive learning based physics module is feasible, practical, and effective for improving conceptual understanding and higher order thingking skills in physics learning. This study provides a significant contribution to the development of innovative learning materials aligned with the demands of the 21st century, offering an alternative solution for creating meaningful, contextual, and critical-thinking-oriented physics learning.